Direction preserving zero point computing and applications (Extended abstract) - Deng, X; Qi, Q; Zhang, J (Springer Berlin Heidelberg, 2009)
We study the connection between the direction preserving zero point and the discrete Brouwer fixed point in terms of their computational complexity. As a result, we derive a PPAD-completeness proof for computing direction preserving zero point, and a matching oracle complexity bound for discrete Brouwer’s fixed point. Building upon the connection between the two types of combinatorial structures for continuous fixed point theorems, we derive an immediate proof that TUCKER is PPAD-complete for all constant dimensions, extending the results of P´alv¨olgyi for 2D case [20] and Papadimitriou for 3D case [21]. In addition, we obtain a matching algorithmic bound for TUCKER in the oracle model